Slikovni radar in radarska interferometrija - Trlep, Darko (Geodetski vestnik, 1997)
In this article the basic principles of imaging radar and radar interferometry are described. Outlined are spaceborne and airborne imaging radar. Different applications of the imaging radar and radar images are presented as well.
Keywords: daljinsko zaznavanje; geodezija; interferometrija; prostorski podatki; radarji